Recent Advances in Patterning Strategies for Full-Color Perovskite Light-Emitting Diodes - Gwang Heon Lee; Kiwook Kim; Yunho Kim; Jiwoong Yang; Moon Kee Choi (Nano-Micro Letters, 2023)
Highlights This article reviews the recent progress in the patterning techniques of metal halide perovskites for full-color displays. Patterning techniques of perovskites are subdivided into in situ crystallization and patterning of colloidal perovskite nanocrystals, including photolithography, inkjet printing, thermal evaporation, laser ablation, transfer printing, and so on. The strength and weakness of each patterning methods are discussed in detail from the viewpoint of their applications in full-color displays.